Societal reintegration following cadaveric orthotopic liver transplantation - Kelly, Ryan (Hepatobiliary Surg Nutr, 2016)
BACKGROUND: Studies on patients’ societal reintegration following orthotopic liver transplantation (OLT) are scarce. METHODS: Between September 2006 and January 2008, all adults who were alive after 3 years post OLT were included in this prospective cohort study. Validated questionnaires were administered to all candidates with the primary aim of investigating the rate of their social re-integration following OLT and potential barriers they might have encountered. RESULTS: Among 157 eligible patients 110 (70%) participated. Mean participants’ age was 57 years (SD 11.4) and 43% were females. Prior to OLT, 75% of patients were married and 6% were divorced. Following OLT there was no significant difference in marital status. Employment rate fell from 72% to 30% post-OLT. Patients who had been employed in either low-skill or advanced-skill jobs were less likely to return to work. After OLT, personal income fell an average of 4,363 Canadian dollars (CAN$) (SD 20,733) (P=0.03) but the majority of recipients (80%) reported high levels of satisfaction for their role in society. CONCLUSIONS: Although patients’ satisfaction post-OLT is high, employment status is likely to be negatively affected for individuals who are not self-employed. Strategies to assist recipients in returning to their pre-OLT jobs should be developed to improve patients’ economical status and societal ability to recoup resources committed for OLT.